Relationship Between the Consumption of Beverage Use and Its Effects on Oral Health: Beverage Consumption and Oral Health - Al Hussaini, Syed Hussain; Shah, Syeda Lalarukh Saba; Shujaat, Nazli Gul; Nasir, Zarish (Pakistan Journal of Health Sciences, 2024)
The current study of beverages as likely contributors to the prevalence of oral diseases in the general population has initiated interest in investigating the association of beverage use and its impact on oral health. Objective: To explore the relationship between beverage consumption and its impact on oral health. Method: Data were gathered from 377 college students for a cross-sectional study by using a convenience sampling technique. The study included male and female students, aged 19-25, excluding those who declined or couldn't communicate in Urdu/English. verbal consent was taken and confidentiality was maintained. A 95% confidence interval and a p-value of equal and < 0.05 were used to identify significant findings. Results: The study included 377 medical and dental college students of which 273 (72.4%) were females and 104 (27.6%) were males. Soft drinks were correlated with dental caries (65.1%) which was followed by sensitivity (14.2%), calculus/plaque (10.7%), and tooth staining (10.1%). Tea consumption was associated with dental caries (54.5%). The relationship between beverage type and its impact on oral health was highly significant (p-value < 0.001). Furthermore, the frequency of beverage consumption and its effect on oral health showed significant results, with a p-value of 0.006. Conclusions: The findings suggest a significant correlation between beverage consumption and various oral health issues, including dental caries, sensitivity, calculus, and staining.